Exploring the potential of microalgae in the recycling of dairy wastes. (December 2020) - Gramegna, G.; Scortica, A.; Scafati, V.; Ferella, F.; Gurrieri, L.; Giovannoni, M.; Bassi, R.; Sparla, F.; Mattei, B.; Benedetti, M.
Abstract: Culturing microalgae using dairy-wastes offers the opportunity of producing valuable biomass for different industrial applications. The capability of four Chlorella species and a recombinant Chlamydomonas reinhardtii strain to mixotrophically grow in wastewaters from an Italian dairy factory was investigated. A robust algal growth could be efficiently sustained in these wastes, despite the abundance of d -Lactose ( 4% w/ v ), that could not be metabolized by any microalgal species. Non axenic cocultivation of microalgae together with microbial communities from the dairy wastes resulted in a marked decrease of their pollution load, thus reducing the necessity of expensive treatments before their discharge in the municipal sewage system. Microalgae cultivated using dairy-wastes were characterized by a lipid content ranging from 12% to 21% (w/w), with Auxenochlorella protothecoides reaching the highest lipid productivity ( 0.16 g/L/d) whereas the transplastomic C. reinhardtii strain expressing a thermostable β-glucosidase reached a recombinant enzyme productivity of 0.18 mg/L/d. Graphical abstract: Unlabelled Image Highlights: A. protot h ec oides grown in dairy wastes displayed highest biomass and lipid yield. Transgenic C. reinhardtii was grown in dairy wastes to produce recombinant proteins. Cocultivation of microalgae and bacteria improved the dairy waste bioremediation. Algal biomass yield sustains the economy of dairy plant-algal cultivation system.